Potential Neurologic Manifestations of COVID-19. Issue 2 (April 2021) - Nordvig, Anna S.; Fong, Kathryn T.; Willey, Joshua Z.; Thakur, Kiran T.; Boehme, Amelia K.; Vargas, Wendy S.; Smith, Craig J.; Elkind, Mitchell S.V.
Abstract : Purpose of Review: Neurologic complications are increasingly recognized in the coronavirus disease 2019 (COVID-19) pandemic. COVID-19 is caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This coronavirus is related to severe acute respiratory syndrome coronavirus (SARS-CoV) and other human coronavirus-related illnesses that are associated with neurologic symptoms. These symptoms raise the question of a neuroinvasive potential of SARS-CoV-2. Recent Findings: Potential neurologic symptoms and syndromes of SARS-CoV-2 include headache, fatigue, dizziness, anosmia, ageusia, anorexia, myalgias, meningoencephalitis, hemorrhage, altered consciousness, Guillain-Barré syndrome, syncope, seizure, and stroke. In addition, we discuss neurologic effects of other coronaviruses, special considerations for management of neurologic patients, and possible long-term neurologic and public health sequelae. Summary: As SARS-CoV-2 is projected to infect a large part of the world's population, understanding the potential neurologic implications of COVID-19 will help neurologists and others recognize and intervene in neurologic morbidity during and after the pandemic of 2020.